Con el corazón desgarrado de dolor: la fotografía postmortem de subadultos durante las primeras décadas del siglo xx en el Perú - Estrada Moreno, Flavio Antonio (2024)
Since its invention, photography has allowed us to build a visual memory of the vital events of our existence and among them the death of a loved one as one of the most dramatic memories that allows us to remember the family member and in turn reminds us of our own inevitable destination. During the 19th and 20th centuries, a practice known as postmortem photography was developed, which was brought from Europe to America, where it developed with its own nuances. In its beginnings, photography was reserved for the most privileged social classes, while the less affluent social classes allocated their resources to preserve the first and only image of the deceased person, which is why this practice had enormous social and psychological importance. This article shows four postmortem portraits of subadult individuals whose data is found in the first two decades of the 20th century in Peru.